The new law on foreign interference – what’s next for businesses - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2021)
In a joint commentary, SMU Associate Professor of Law Eugene Tan and SMU Assistant Professor of Law Benjamin Joshua Ong discussed what the Foreign Interference (Countermeasures) Bill (Fica) means for businesses. They opined that businesses could have disclosure policies for themselves and their stakeholders, akin to conflict of interest disclosures. They also noted that more can be done to clarify the limits to government powers under Fica, and pointed out that conversations about foreign interference must go beyond Fica.